Justice perverted sex offense law, psychology, and public policy - Ewing, Charles Patrick, 1949- (New York ; Oxford : Oxford University Press, 2011)
In 'Justice Perverted', Charles Patrick Ewing draws on research from across the social and behavioural sciences, and weighs the evidence for the spectrum of sex offence laws. A rational look at an intensely emotional subject, 'Justice Perverted' is an essential book for anyone interested in the science behind public practice.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Keywords: Sex offenders -- Psychology; Sex offenders -- Legal status, laws, etc. -- United States; Sex offenders -- Government policy -- United States